2007
DOI: 10.1055/s-2006-924028
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Oligomers in Human Serum during Acute and Chronic Exercise: Relation to Lipid Metabolism and Insulin Sensitivity

Abstract: Beneficial effects of physical exercise include improved insulin sensitivity, which may be affected by a modulated release of adiponectin, which is exclusively synthesized in white adipose tissue and mediates insulin sensitivity. Adiponectin circulates in three different oligomers, which also have a distinct biological function. We therefore aimed to investigate the distribution of adiponectin oligomers in human serum in relation to physical activity. Thirty-eight lean and healthy individuals were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…Blüher et al (27) found that HMW adiponectin concentration increased with exercise treatment even in subjects with normal glucose tolerance. In contrast, Bobbert et al (28) showed that HMW adiponectin concentration was similar before and after 6 weeks of marathon training without a reduction in body weight. In the present study, HMW adiponectin concentration increased in the exercise group, although this increase did not reach significance during the aerobic exercise program (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Blüher et al (27) found that HMW adiponectin concentration increased with exercise treatment even in subjects with normal glucose tolerance. In contrast, Bobbert et al (28) showed that HMW adiponectin concentration was similar before and after 6 weeks of marathon training without a reduction in body weight. In the present study, HMW adiponectin concentration increased in the exercise group, although this increase did not reach significance during the aerobic exercise program (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In a 120-min cycling program, healthy male subjects showed no significant changes in plasma adiponectin during the exercise program and throughout the post-exercise recovery period compared to baseline levels [85]. Furthermore, no significant changes in serum adiponectin or oligomer composition were observed following acute cycling in eight healthy men [86].…”
Section: Circulating Adiponectin and Acute Exercisementioning
confidence: 84%
“…Previous reports from various protocol studies indicate that adiponectin levels do not change in healthy non-obese humans regardless of their improved insulin sensitivity, and suggest that a direct effect of exercise training on adiponectin levels is unlikely to represent the mechanisms of improved insulin resistance 8,[15][16][17] ; however, in insulin-resistant subjects, exercise training is recommended as a therapy to improve insulin resistance 18,19) , but previous studies in overweight and/or diabetic subjects have reported conflicting results 8,19,20) . The presence or absence of body weight loss after exercise training may not necessarily determine whether exercise training can increase serum adiponectin levels, but exercise training can exert a presumable effect on serum adiponectin levels in insulin-resistant and obese individuals through the reduction of fat mass with body weight loss 8,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%